Innovative Entrepreneurship for Online Business: Qualitative Study - Hermawan, Iwan; Hindrawati, Gita; Inayah; Suharmanto (Conference Series, 2021)
Entrepreneurship in online business is related to the rapidly growing number of internet literacy in Indonesia. Currently, 160 million people access the internet, making Indonesia an economical cake that creates a potential market. It encourages market competition and innovation in the red zone. Competition triggers business actors, including entrepreneurs, to rethink the strategies applied to win market competition relevant to the current phenomenon. The research question is related to how online business entrepreneurs take advantage of innovation to survive the business turbulence, such as developing technology, changing regulations, market tastes, and the need for social distancing in a pandemic situation. Innovative Entrepreneurship (IE), initially inspired by Schumpeter and Lumpkin Dess, is now further transformed by the evolution of generations from generation X to generation Y (millennial generation). Millennials have different characters and lifestyles, so that in terms of entrepreneurial characteristics, millennials have an IE perspective that brings their uniqueness. In line with the development of the internet and application breakthroughs by unicorn developers, E-marketplaces have become an interesting online business phenomenon to explore and create the dynamics of IE. This study is based on the perspective of technology-based entrepreneurship through a qualitative approach. The results of the study obtained an IE construct with millennial ownership. The construct of IE in the online business environment is formed by four dimensions, namely technology, work atmosphere, organizational strategy, and market agility. By applying these four dimensions, the IE construct will foster entrepreneurship to formulate better ways to survive and win the competition in the e-marketplace business environment.